Immigrant labour market assimilation and arrival effects: evidence from the UK labour force survey - Ken Clark; Joanne Lindley (Institute for the Study of Labor (IZA), 2006)
We estimate models of earnings and employment outcomes for a sample of white and non-white male immigrants drawn from the Labour Force Survey between 1993 and 2002. Immigrants who arrived to enter the labour market are distinguished from those who arrived to complete their education. Diverse patterns of labour market assimilation are found depending on ethnicity and immigrant type. Whites tend to do better than non-whites and labour market entrants do worse than education entrants. There is some evidence of unemployment rates at time of entry to the labour market being associated with permanently lower earnings for non-white immigrants.
Keywords: J23; J7; 330; immigrants; assimilation; earnings; employment; Migrationspolitik; Beschäftigungseffekt; Lohndifferenzierung; Ethnische Gruppe; Schätzung; Großbritannien